2017
DOI: 10.1155/2017/9413060
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Simulation Research on the Influence of Stirring Parameters on the Distribution of Particles in Cast SiCp/A356 Composites

Abstract: Achieving the uniform distribution of reinforcement particles in MMCs is very important for the effect of stirring parameters and the flow action of the melt, which should be known. The effect of stirring parameters on the distribution of SiC particles in SiCp/A356 composites was studied by the experimental and numerical methods in this paper. The experimental results show the SiC distribution with different stirring parameters. In addition, the effects of the fluid velocity and volume fraction of SiC particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…e different positions of the volume fraction of SiC were controlled at different stirring temperatures, stirring speeds, and stirring times. ey concluded that according to the simulation of the shearing force, moments, and stirring power of the stirring rod the SiC is unwell dispersed at the position closer to the stirring rod without analyzing it [11]. Figure 14 shows the stirring rod and its position when the stirring rod and its blades dimensions are unclear but from the figure it seems it has two stages.…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 99%
See 3 more Smart Citations
“…e different positions of the volume fraction of SiC were controlled at different stirring temperatures, stirring speeds, and stirring times. ey concluded that according to the simulation of the shearing force, moments, and stirring power of the stirring rod the SiC is unwell dispersed at the position closer to the stirring rod without analyzing it [11]. Figure 14 shows the stirring rod and its position when the stirring rod and its blades dimensions are unclear but from the figure it seems it has two stages.…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 99%
“…e proper design of experiments was not used by many researchers, so there is no clarification and analysis of the interactions between the various inputs [8][9][10]. Authors investigated that the stirring casting process is not obvious enough, and the reason behind the particle distribution is not comprehended for the aluminum ceramic powder composite [11]. In addition, the researchers analyzed the complexity and difficulty of understanding the SiC particles distribution process in the aluminum alloy, including the interaction between particles themselves and with the matrix alloy [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Сообщается, что агломерации частиц в некоторых случаях удается избежать путем увеличения длительности перемешивания до 20 мин и более [22], однако при этом одновременно возрастает риск коробления, частичного растворения и эрозионного разрушения материала импеллера, а также усиления химических реакций между частицами и расплавом. На стадии приготовления композиционного расплава распределение частиц в матричном сплаве определяется такими факторами, как вязкость композиционной суспензии, эффективность перемешивания с позиций разрушения агломератов, а также захват газов при замешивании частиц и характеристики частиц, влияющие на скорость их седиментации [23]. Проведенные эксперименты показывают, что в ходе повторных переплавов происходят процессы перераспределения армирующих частиц, приводящие к разрушению агломератов даже в отсутствие интенсивного перемешивания импеллером.…”
Section: результаты и их обсуждениеunclassified